Credit risk and operational risk on financial performance of universal banks in Ghana: A partial least squared structural equation model (PLS SEM) approach - Samuel Gameli Gadzo; Holy Kwabla Kportorgbi; John Gartchie Gatsi (Cogent Economics & Finance, 2019)
In recent years, financial institutions especially universal/commercial banks across Africa have been faced with forceful mergers and acquisitions. These occurrences impede the level of financial inclusion and reduces public confidence in the financial system as a whole. This study assessed the effect of credit and operational risk on the financial performance of universal banks in the context of the structural equation model (SEM). Data were collected from all the 24 universal banks in Ghana without missing variables and using the PLS-SEM, the results showed that credit risk influences financial performance negatively contrary to the empirical study but in line with the information asymmetry tenant of the lemon theory. It was also found that operational risk influences the financial performance of the universal banks in Ghana negatively. Furthermore, the study indicated that bank specific variables measured by (asset quality, bank leverage, cost to income ratio and liquidity) significantly influence credit risk, operational risk as well as the financial performance of the universal banks positively. We recommend that banks be encouraged to cut-down their lending rates in other to decrease credit risk and subsequently boost profitability. Regarding operational risk, banks should reduce leverage and have their portfolio more concentrated on liquid investment income so as to boost profitability.
Keywords: 330; operational risk; credit risk; PLS SEM; panel regression; lemon theory